EFEKTIVITAS DANA BOS DALAM MENINGKATKAN MUTU PENDIDIKAN DASAR: ANALISIS LITERATUR EMPIRIS TAHUN 2015-2025 - Theoline, Easyah; Ahmad, Masduki; Soraya, Evitha (STKIP Pesisir Selatan, 2025)
This study aims to answer these questions through a systematic analysis of empirical literature published in the period 2015–2025. Given the importance of evidence-based policies, this study is expected to provide comprehensive insights into the effectiveness of BOS Funds and become a basis for more targeted and equitable education policy reforms. Using a systematic literature review method, this article examines seven main sources that include quantitative, qualitative, and mixed approaches. The focus of the study is directed at quality indicators such as the learning process, facilities and infrastructure, and education governance. The results of the study indicate that BOS Funds generally contribute to improving the quality of the teaching and learning process and education facilities. However, there are still significant gaps in the effectiveness of implementation, especially between developed regions and 3T (disadvantaged, outermost, and frontier) regions, as well as weak accountability and reporting systems for the use of funds. This study recommends reformulating BOS policies based on local needs and improving the monitoring system through digitalization. This article is expected to contribute to the formulation of evidence-based policies for increasing basic education funding in Indonesia.